Accessible tourism and formal planning: Current state of Istria County in Croatia - Damir Popović; Iva Slivar; Marli Gonan Božac (Administrative Sciences, 2022)
When the number of older people and the number of families with young children (babies and toddlers) are counted in the total share of persons with disability it is clear that a significant share of people in the world's tourist market face various obstacles to achieving their fundamental human rights in accessing tourist destinations and related infrastructure. These segments of the market encounter various challenges when they do travel, while many refrain from travelling at all. The theoretical framework examines the concept of accessible tourism and provides a review of the necessary preconditions for forming such a tourist offer available to everyone. Contrary to common belief, accessible tourism surpasses the issues of mobility, as it also includes people with mental, mood, vision, speech, hearing, stroke and other conditions. Examples of good practice are also provided as an incentive for the design and implementation of future inclusive projects, representing the aim of this paper. Research featuring various categories of the tourism offer available to everyone on the case study of Istria County is also presented. The analysis compares major towns in Istria County and the degree of their adaptation to the needs of this market segment, where many practical implications have emerged. The concept of accessibility lies on three key pillars: physical, informative and service based. Thus, removing physical barriers, incorporating the principles of universal design into every new building's design, as well as educated staff for formulating and implementing strategies and other plans, are key factors in creating additional tourist value. It is fundamental to include people with disabilities in tourism and in society.
Keywords: 350; accessible tourism; disability; formal planning; Istria County; mobility; people with special needs